Machinery Healt Monitoring System with Arduino - Abdul Ghofir; Enda Phramoedya (IT for Society, 2020)
Machinery safety is the most important aspectneeded around manufacturing or other engineering equipment.Machine guarding provides a means to protect humans frominjury while working nearby or while operating equipment.Machinery that has rotary part such as turbines, pumps, fans,rollers, are needed to be monitored to report the vibrationwhether they are safety or not. Thus the preventive action isneeded to ensure the safety of machinery before being used. Thispaper is about the monitoring system for machinery healthwhich is developed with Arduino. It detects the vibration fromthe machine and information to mobile application. Theinformation may include the vibration pattern, acceleration (g)value, recorded event, and also gives alert via mobile applicationin the form of vibration and ringtone.